2015
DOI: 10.1016/j.jadohealth.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Parental Separation, Parental Alcoholism, and Timing of First Sexual Intercourse

Abstract: Purpose We examined timing of first voluntary sexual intercourse as a joint function of parental separation during childhood and parental history of alcoholism. Methods Data were drawn from a birth cohort of female like-sex twins (n=569 African Ancestry [AA], n=3415 European or other Ancestry [EA]). Cox proportional hazards regression was conducted predicting age at first sex from dummy variables coding for parental separation and parental alcoholism. Propensity score analysis was also employed comparing int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Previous studies have invariably focused on only the socio-cultural determinants of AFS and the relevance of early AFS to poor educational achievement and other adverse outcomes12,13. We recognise the importance of diverse socio-cultural factors, which are reflected by the discordant changes in AFS and AFB seen by year of birth in the UK Biobank study (Figure S4).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have invariably focused on only the socio-cultural determinants of AFS and the relevance of early AFS to poor educational achievement and other adverse outcomes12,13. We recognise the importance of diverse socio-cultural factors, which are reflected by the discordant changes in AFS and AFB seen by year of birth in the UK Biobank study (Figure S4).…”
Section: Discussionmentioning
confidence: 93%
“…In particular, parental and peer norms and behaviours have a strong influence on teenagers’ sexual behaviour14–16. Twin studies have suggested some genetic contribution to AFS17,18, however observations of older AFS among monozygous compared to dizygous twins13 casts doubt on the validity of twins studies to accurately estimate the heritability of this trait.…”
Section: Introductionmentioning
confidence: 99%
“…First, logistic regression analyses were used to examine the association between low parental monitoring and early substance use without and with covariate adjustment. Next, consistent with earlier work (e.g., Waldron et al, 2014Waldron et al, , 2015, PSA was conducted to compare adolescents who reported low parental monitoring (lowest 25% within racial/ethnic group) and those who reported higher parental monitoring (upper 75%) based on their predicted probability of experiencing low parental monitoring. PSA is a statistical technique that can be used to reduce bias from confounding variables by matching groups on a range of highly correlated risk factors presumed to predate exposure (Green & Stuart, 2014;Rosenbaum, 2010;Rosenbaum & Rubin, 1983;West et al, 2014), in this case, to low parental monitoring.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Indeed, adverse childhood experiences have been shown to associate with earlier age at menarche, the start of a woman's sexual maturity and reproductive potential (5). Age at first sexual intercourse is also related to the childhood environment (6)(7)(8). Whilst adopting a fast life history strategy may increase fitness, it may also have costs to the individual such as those associated with teenage pregnancy and risky behaviours such as violence, criminality, and substance abuse (3,9,10)).…”
Section: Introductionmentioning
confidence: 99%